2000
DOI: 10.1021/ma991556d
|View full text |Cite
|
Sign up to set email alerts
|

Poly(diaryl)stannanes:  Influence of Substituents on the σσ* Transition Energy

Abstract: Poly(diaryl)stannanes were prepared by the dehydropolymerization of secondary hydrostannanes Ar2SnH2 with dimethylzirconocene catalyst. At room temperature, H(Ar2Sn)nH polystannanes (Ar ) p-t Bu-C6H4, p-n Hex-C6H4, o-Et-C6H4, o-Et-p-n BuO-C6H3, p-n BuO-C6H4, p-(Me3Si)2N-C6H4) exhibit λmax values attributed to σ f σ* transitions in the range 430-506 nm. These values vary according to the polymer molecular weights and are independent of temperature between -20 and 90 °C. A sample of poly[bis(o-ethyl-p-n butoxylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 36 publications
2
102
0
Order By: Relevance
“…In order to circumvent this problem, monomeric diarylstannanes Ar 2 SnH 2 with the solubilizing substituents Ar = p-t-BuC 6 H 4 , p-n-HexC 6 H 4 , o-EtC 6 H 4 , p-n-BuOC 6 H 4 , o-Et,p-t-BuC 6 H 3 and p-(Me 3 Si) 2 NC 6 H 4 were used in the Cp 2 ZrMe 2 -catalysed dehydropolymerization 97,100 .…”
Section: Polystannanesmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to circumvent this problem, monomeric diarylstannanes Ar 2 SnH 2 with the solubilizing substituents Ar = p-t-BuC 6 H 4 , p-n-HexC 6 H 4 , o-EtC 6 H 4 , p-n-BuOC 6 H 4 , o-Et,p-t-BuC 6 H 3 and p-(Me 3 Si) 2 NC 6 H 4 were used in the Cp 2 ZrMe 2 -catalysed dehydropolymerization 97,100 .…”
Section: Polystannanesmentioning
confidence: 99%
“…It was concluded that polystannanes are stable towards oxygen but extremely reactive to moisture. In solution, poly(diaryl)stannanes as well as poly(dialkyl)stannanes photochemically degrade to give cyclic oligomers, predominantly the pentamer and the hexamer 82,90,100 . Exposure of H[(p-t-BuC 6 H 4 ) 2 Sn] n H in THF to light for 30 min resulted in complete degradation to give a mixture of cyclic oligomers 100 .…”
Section: Polystannanesmentioning
confidence: 99%
See 2 more Smart Citations
“…[13,14] However, most of these reactions suffered from drawbacks such as pronounced formation of cyclic stannanes as byproducts, low yields, low molecular weights or poor reproducibility. In addition, while poly(dialkylstannane)s have been extensively studied, [1,3,6 -8,10 -12,15 -18] the synthesis of poly(diarylstannane)s has been little considered owing to the insolubility of typical representatives like poly(diphenylstannane), [19] and therefore the material properties of well-defined poly(diarylstannane)s have still been modestly explored.…”
Section: Introductionmentioning
confidence: 99%